Osteopathic Palpation of the Heart - Bordoni, Bruno (Cureus, 2021)
In the panorama of scientific literature, there is a paucity of literature on how to palpate the heart area in the osteopathic setting and relevant indications on which palpatory sensations the clinician should perceive during the evaluation. The article reviews the fascial anatomy of the heart area and the heart movements derived from magnetic resonance imaging (MRI) studies and describes the landmarks used by the cardiac surgeon to visualize the mediastinal area. The text sets out possible suggestions for a more adequate osteopathic palpatory evaluation and describes any tactile sensations arising from the patient's chest. To the knowledge of the authors, this is the first article that seeks to lay solid foundations for the improvement of osteopathic manual medicine in the cardiology field.